Incidence of cholelithiasis in the northern part of Thailand - Prathnadi P. (2014)
It may be concluded from comparisons of recent u/s examinations in Northern Thailand to studies in Japan and to the gallstone study conducted over two decades ago that gallstone disease in Thailand is starting to exhibit the same situation as in the West. In comparing overall rates over time the gallstone incidence in Thailand appears to have climbed from 2.61 to 3.10 per cent (Fig. F). The rate increase is even more significant when broken down by sex (male: 1.89%--> 2.50%, female: 3.23%--> 3.70%). In addition, the present rates of female and male gallstone incidence in Northern Thailand closely match the rates found in studies of the Japanese population. Because gallstone disease has become a major public health problem in the West, a number of studies have emphasized the epidemiological characteristics of the disease in order to implement controls. As Thailand's gallstone problem seems to be heading towards the same level of importance further studies involving epidemiological factor linkage may be necessary and the technological advances in Ultrasonography make such studies quite feasible.